Q: What is -9 x 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

9(6 + x) = 1

because they divide into 6 evenly - no remainder

X + 6*9 = X + 54

9 + x = 3 x = 3-9 x = -6 Check 9 + (-6) = 3 9 - 6 = 3

9 x 6 = 54

Commutative

[(√9)! X (√9)!] + 9 + (√9)! = [6 X 6] + 9 + 6 = 51 Note: It can also be done with just three 9s. [(√9)! x 9] - √9 = [6 x 9] - 3 = 51

1 x 6 = 6 6 x 9 = 54 54 - 4 = 50 So: 1 x 6 x 9 - 4 = 50

66.6666666% 6/9 = x/100 : x = 100 * (6/9) = 66.67 %

9 + 6% = 9 x (1 + (6/100)) = 9 x 1.06 = 9.54

96 = 9 x 9 x 9 x 9 x 9 x 9 = 531441

9^6